PENGARUH UPAH DAN INVESTASI TERHADAP KETIMPANGAN PENDAPATAN DAN KESEJAHTERAAN MASYARAKAT KABUPATEN KOTA DI PROVINSI BALI - Sebo, Alldy Jaya Nugraha; Sukadana, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 9 (2022): VOL11NO 9, SEPTEMBER 2022 [3325-3700]DO - 10.24843/EEP.2022.v11.i09.p08, 2022)
Equitable and equitable economic development mandates development programs that encourage increased regional economic growth, eliminate inequality and can improve community welfare in a sustainable manner. This study aims to determine the effect of wages and investment on income inequality and the welfare of the district/city community in Bali Province. The source of the data used in this study is panel data of 63 data from 2015-2021 in 9 districts/cities in Bali, the method of collecting data is non-participant observation by observing documents related to the research. The data analysis technique used is path analysis technique. The results show that wages have a negative and significant effect on income inequality, while investment has a positive and significant effect on income inequality in the districts/cities of Bali Province. Wages and investment have a positive and significant effect on people's welfare, while income inequality has a positive but not significant effect on people's welfare in the districts/cities of Bali Province. Income inequality does not mediate the effect of wages and investment on welfare   Keywords: wages, investment, inequality, welfare.